2014
DOI: 10.1007/s11060-014-1474-6
|View full text |Cite
|
Sign up to set email alerts
|

The proteomic response in glioblastoma in young patients

Abstract: Increasing age is an important prognostic variable in glioblastoma (GBM). We have defined the proteomic response in GBM samples from 7 young patients (mean age 36 years) compared to peritumoural-control samples from 10 young patients (mean age 32 years). 2-Dimensional-gel-electrophoresis, image analysis, and protein identification (LC/MS) were performed. 68 proteins were significantly altered in young GBM samples with 29 proteins upregulated and 39 proteins downregulated. Over 50 proteins are described as alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…Also, through the in silico approach, we tried to gain some insight into the alternative metabolic routes and metabolites which contributed to the metabolic heterogeneity of glioblastoma. The present model was capable of yielding results which were in correspondence to the experimentally proved phenomena of both astrocytes and glioblastoma (Deighton et al 2014;Mangia et al 2009;Marrif and Juurlink 1999;Pellerin and Magistretti 1994;Wise et al 2008;Zhou et al 2011). From our study, specific pathways were observed to demonstrate a co-operative effect in the astrocyte and glioblastoma scenarios.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Also, through the in silico approach, we tried to gain some insight into the alternative metabolic routes and metabolites which contributed to the metabolic heterogeneity of glioblastoma. The present model was capable of yielding results which were in correspondence to the experimentally proved phenomena of both astrocytes and glioblastoma (Deighton et al 2014;Mangia et al 2009;Marrif and Juurlink 1999;Pellerin and Magistretti 1994;Wise et al 2008;Zhou et al 2011). From our study, specific pathways were observed to demonstrate a co-operative effect in the astrocyte and glioblastoma scenarios.…”
Section: Discussionsupporting
confidence: 75%
“…For the verification of the objective function-'GBM_BM' in representing the properties of glioblastoma, a qualitative analysis was performed to compare the activity of certain reported reactions in the astrocytic and glioblastoma scenario. The fold change in activity from astrocytic to glioblastoma scenario as predicted from the model was compared to existing proteome data extracted from young glioblastoma patients (Deighton et al 2014). The results of this comparison are listed in Table 1.…”
Section: Validation Of Glioblastoma Metabolic Demand Reaction (Gbm_bm)mentioning
confidence: 99%
“…Other important individual prognostic factors are the age of diagnosis, the Karnofsky performance status and the methylation status of the MGMT promoter gene [65]. A comparative proteomic analysis of young and old glioblastoma patients identified multiple differentially expressed proteins involved in the regulation of the tumorigenesis that could explain the prognostic differences between young and old glioblastoma patients [38]. Among the differentially expressed proteins of special interest is the Phosphatidylethanolamine-binding protein 1 (PEBP1), an inhibitor to both Raf/MEK/ERK and nuclear factor kappa B pathways [66].…”
Section: Diffuse Astrocytic and Oligodendroglial Tumorsmentioning
confidence: 99%
“…Among the differentially expressed proteins of special interest is the Phosphatidylethanolamine-binding protein 1 (PEBP1), an inhibitor to both Raf/MEK/ERK and nuclear factor kappa B pathways [66]. PEPB1 was up-regulated in young glioblastoma and down-regulated in old glioblastoma patients [38]. The regulation differences of PEPB1 between young and old glioblastoma patients should be further investigated to understand its influence on prognosis.…”
Section: Diffuse Astrocytic and Oligodendroglial Tumorsmentioning
confidence: 99%
“…It has also been shown that NF-kB induces cancer development and tumor progression by inducing a proinflammatory microenvironment and even leads to chemotherapy resistance (4,43). NF-kB regulates protein transcription for the down-regulation of apoptosis and increases cell invasion, angiogenesis, and vascular permeability in the cell nucleus (12). Chin et al reported the neuroprotector effect of GSK-3 inhibition in that it reduces neuronal death (8).…”
Section: █ Conclusionmentioning
confidence: 99%